’Backrooms’ Tests the Future of Horror Movies - Schriefer, Natalie (Bloomberg.com, 2026)
The film may determine how much Hollywood is willing to bet on other stories without a clear monster.
Keywords: A24; Backrooms; Bloomberg Graphics; Hollywood; Theater; culture; dept.hhs; gaming; graphic; indie games; internet; movies; opinion column